2021
DOI: 10.21601/ijese/10934
|View full text |Cite
|
Sign up to set email alerts
|

Reconnecting Children with Nature: Foundation and Growth of the Nature Schools Movement in Iran

Abstract: The Nature Schools movement in Iran commenced in 2014 and expanded steadily for half a decade, growing to almost 100 schools. Emulating similar educational inititives in Europe and North America, Nature Schools offered outdoor educational experiences for pre-school and primary school years, spreading across both metropolitan and regional Iran. Before the first Nature Schools were started, detailed initial planning between academics and the government Environment Department and Education Ministry was undertaken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The structure of learning interactions underwent great pressure due to the sharply increased demand for an individual approach to the pupils, especially to those with health limitations [32][33][34][35][36]. The teacher's work and his/her communication with the pupils have become unprecedentedly open to the attention of parents.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of learning interactions underwent great pressure due to the sharply increased demand for an individual approach to the pupils, especially to those with health limitations [32][33][34][35][36]. The teacher's work and his/her communication with the pupils have become unprecedentedly open to the attention of parents.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that spending time in nature can improve cognitive function, increase creativity, reduce stress, and improve physical health (Muafiah, Afifah, Nurohman, Huda, & Siswadi, 2021). Nature-based learning can also foster a sense of connectedness and responsibility to the environment, as well as helping students develop skills such as problem solving, teamwork and critical thinking (Burns & Manouchehri, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The nature school concept is adopted in several countries, including Ireland, Iran and the UK. For example, the existence of nature schools in Iran is based on the fact that urban areas as a result of modernization, do not effectively support child presence and activities (Burns and Manouchehri, 2021). Burns and Manouchehri, 2021).…”
Section: Literature Review Learning Process In Nature Schoolmentioning
confidence: 99%
“…For example, the existence of nature schools in Iran is based on the fact that urban areas as a result of modernization, do not effectively support child presence and activities (Burns and Manouchehri, 2021). Burns and Manouchehri, 2021). Due to the capital's and other major cities' high air pollution levels, declining urban green spaces brought on by land use change, and water shortages, schools have been forced to close (Staff, 2017;Novo, 2019).…”
Section: Literature Review Learning Process In Nature Schoolmentioning
confidence: 99%